Pygommatius Scarbrough & Marascia, a valid ommatiine genus (Diptera: Asilidae) with new combinations and new species from the Philippines - Scarbrough, A. G.; Hill, H. (Zootaxa, 2005)
The subgenus Pygommatius Scarbrough & Marascia of Ommatius Wiedemann is elevated to genus based upon the following combination of characters: thick pencil-like bristles of the face, unusually stout erect bristles on two or three sternites, absence of a stout anepimeral bristle, deeply trilobed epandrium, the first branch being very short, a minute gonostylus, unusually long ejaculatory apodeme, and two pairs of ligament-like apodemes along the posterior margin of the aedeagal sheath. Thirty-five species are transferred from Ommatius to Pygommatius as new combinations and four new species from the Philippines (apoticius, iriga, misamis, and montanus) are described, increasing the number of species within the genus to 39. Formally known only from the Afrotropical Region, this is the first record of Pygommatius in the Oriental Region. Previously described species from the Philippines are reviewed and terminalia of the four new species are illustrated. A key to the nine Philippine species is also provided.